give me proper answre
Attachments:
![](https://hi-static.z-dn.net/files/d95/40a97cfb46e26547b0f4997c4333ccf2.jpg)
Answers
Answered by
2
Answer:
In ∆ABD and ∆ACD
AD=AD. (common)
AB=AC. (given)
angle C = angle B. (angle opposite to equal sides are equal)
therefore ∆ABD ≈∆ACD
So, BD=CD. (by cpct)
angle BAD = angle CAD. (by cpct)
hence proved
if it helped you mark it as brainliest answer and follow
Answered by
1
Answer:
here is your proper answer..
please mark it as brainliest plz plz...
Hope it will help you...
Thank you...❤️
Attachments:
![](https://hi-static.z-dn.net/files/da2/bc7aecc39643524447f301aad91b0be0.jpg)
Similar questions